2011
DOI: 10.1111/j.1440-172x.2010.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and quality of recovery in day surgery: A questionnaire study using Hospital Anxiety and Depression Scale and Quality of Recovery Score

Abstract: The aims of this study were (i) to examine the association between preoperative and postoperative anxiety, and (ii) to examine the association between preoperative anxiety and postoperative recovery, following day surgery under general anaesthesia. Day surgery has become more commonplace owing to advances in pharmacology, anaesthetic and surgical techniques, as it has recognized benefits, such as lower costs and reduced incidence of infection. Recent years have seen increased complexity of day surgery undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 26 publications
1
29
0
2
Order By: Relevance
“…A study from India showed that preoperative contact did not decrease anxiety; however, intraoperative psychological support, showing the baby to her mother and early breastfeeding were related to patient satisfaction in patients undergoing caesarean delivery under spinal anaesthesia (16). Another analysis including 1793 patients in 22 studies showed that when women were asked which mode of anaesthesia they would prefer in subsequent surgery, those who received general anaesthesia stated that they would prefer general anaesthesia again (17 A study from England evaluated anxiety levels and recovery scores and showed that anxiety levels were high in women preoperatively and dropped significantly postoperatively (9). The same study concluded that preoperative anxiety had no effect on recovery scores, but postoperative anxiety levels were correlated with recovery scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study from India showed that preoperative contact did not decrease anxiety; however, intraoperative psychological support, showing the baby to her mother and early breastfeeding were related to patient satisfaction in patients undergoing caesarean delivery under spinal anaesthesia (16). Another analysis including 1793 patients in 22 studies showed that when women were asked which mode of anaesthesia they would prefer in subsequent surgery, those who received general anaesthesia stated that they would prefer general anaesthesia again (17 A study from England evaluated anxiety levels and recovery scores and showed that anxiety levels were high in women preoperatively and dropped significantly postoperatively (9). The same study concluded that preoperative anxiety had no effect on recovery scores, but postoperative anxiety levels were correlated with recovery scores.…”
Section: Discussionmentioning
confidence: 99%
“…Further, satisfaction with the mode of anaesthesia was related to emotional status and pain subgroups of QoR-40 in Group SA. There was no relationship (9,10). Emergency caesarean delivery is an immediate decision; psychological or preoperative preparation is not sufficient in such cases and it is associated with a risk of foetal-maternal mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety should be identified as a risk factor and predictor of suboptimal outcomes and should not be ignored. 9 Patients who have a lack of knowledge into their postoperative recovery trajectory can have compromised comfort and satisfaction levels as this gap can exacerbate anxiety and hinder their recovery. 1 PA nurses are the ambassadors for patient safety, ensuring that health teaching is one of the multimodal pain management strategies used to facilitate a smooth recovery process at home.…”
Section: Communication Is the Keymentioning
confidence: 99%
“…Waiting for and undergoing day surgery might lead to feelings of anxiety and fear (McIntosh and Adams, 2011). According to Haugen et al (2009) patients with regional anaesthesia experienced the highest level of anxiety at induction of anaesthesia.…”
Section: Introductionmentioning
confidence: 99%